2016
DOI: 10.1016/j.serj.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Reactive Black 5 by Aeromonas hydrophila strain isolated from dye-contaminated textile wastewater

Abstract: Aeromonas hydrophila isolate showed the best decolorization of Reactive Black 5 (RB5) at the concentration of 100 mg L -1 on modified mineral salt medium among 42 bacterial isolates. Optimization of parameters for RB5 dye decolourization was studied under static condition. Under optimized condition, decolorization efficiency of RB5 by A. hydrophila was found to be 76% at 100 mg L -1 within 24 h. The optimum pH and temperature for the decolorization was 7 and 35 °C respectively. Biodegradation and decolorizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(91 citation statements)
references
References 23 publications
7
66
0
2
Order By: Relevance
“…The experiment is performed for an initial dye solution of 50 mg/L supplemented with peptone (5 g/L), yeast extract (5 g/L), and salt (3 g/L) at pH 10 and incubation temperature of 40 °C for 48 h. Consequently, the decolourization percentage of the MO dye is obtained ∼85 % under static condition and 61 % under shaking condition. The present result represents a similarity with the reported result by Bouraie and Din, who concluded the higher decolourization of Reactive Black‐5 azo dye by Aeromonas hydrophila under a static condition than shaking condition. According to Oturkar et al, the lower decolourization percentage might be obtained under a shaking aerobic state, due to the lower activity of the azoreductase enzyme of the bacterial strain.…”
Section: Resultssupporting
confidence: 93%
“…The experiment is performed for an initial dye solution of 50 mg/L supplemented with peptone (5 g/L), yeast extract (5 g/L), and salt (3 g/L) at pH 10 and incubation temperature of 40 °C for 48 h. Consequently, the decolourization percentage of the MO dye is obtained ∼85 % under static condition and 61 % under shaking condition. The present result represents a similarity with the reported result by Bouraie and Din, who concluded the higher decolourization of Reactive Black‐5 azo dye by Aeromonas hydrophila under a static condition than shaking condition. According to Oturkar et al, the lower decolourization percentage might be obtained under a shaking aerobic state, due to the lower activity of the azoreductase enzyme of the bacterial strain.…”
Section: Resultssupporting
confidence: 93%
“…Various methods such as coagulation/flocculation [2], biodegradation [3], adsorption [4][5][6], membrane separation [7], photocatalysis [8][9][10], and ozonation [11] have been used for removal of synthetic dyes from waters and wastewaters. Among all these methods, adsorption has been found to be one of the most common techniques for dye removal because of its easy operation and effectiveness.…”
mentioning
confidence: 99%
“…HPLC‐MS analysis was used to identify the degradation products and the mass spectroscopy obtained was shown in Figure S2. It was indicated that one product with m/z ratio of 282 was related to 1‐sulphonic, 2‐(4‐aminobenzenesulphonyl) ethanol resulted from N=N cleavage in molecular structure, as one of the degradation products of dyes by ZVI/Cu (Satapanajaru, Chompuchan, Suntornchot, & Pengthamkeerati, ; Samiee, Goharshadi, & Nancarrow, ; El Bouraie & El Din, ;). The product with m/z ratio of 142 was corresponded to Muconic acid (He, Song, Zhou, Ying, & Chen, ), and the product with m/z ratio of 323 possibly suggested 1,2,7‐triamino‐8‐hydroxynapthalene‐3,6‐disulfonic acid (TAHNDS) can act as mediators stimulate to the degradation of RB (Wang, Cheng, & Sun, ).…”
Section: Resultsmentioning
confidence: 99%